1995
DOI: 10.1002/jnr.490420506
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor induces functional expression and phenotypic differentiation of cultured fetal neuropeptide Y‐producing neurons

Abstract: A series of studies from our laboratory has established an aggregate culture system of fetal rat brain cells that can serve as a model for studying regulatory processes of the developing neuropeptide Y (NPY)-producing neurons. Using aggregate cultures derived from 17-day-old fetal rat cortex, we addressed these questions: 1) Does brain-derived neurotrophic factor (BDNF) stimulate NPY production, and if so, is stimulation a function of the developmental state of the cultured NPY neuron? 2) Does BDNF induce phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 43 publications
5
24
1
Order By: Relevance
“…The specificity of this effect was highlighted by the lack of any increase in somatostatin content in NGF-treated cultures. Furthermore, these data are in line with the results of previous studies, where NGF was shown to have no effect on peptidergic neurons (31). Examination of somatostatinimmunopositive neurons, after BDNF or NT-3 treatment, indicated no change in the number of somatostatin neurons; but the immunoreactivity in each somatostatin neuron was intensified, suggesting that the somatostatin level was increased in each neuron by NTs.…”
Section: Discussionsupporting
confidence: 81%
“…The specificity of this effect was highlighted by the lack of any increase in somatostatin content in NGF-treated cultures. Furthermore, these data are in line with the results of previous studies, where NGF was shown to have no effect on peptidergic neurons (31). Examination of somatostatinimmunopositive neurons, after BDNF or NT-3 treatment, indicated no change in the number of somatostatin neurons; but the immunoreactivity in each somatostatin neuron was intensified, suggesting that the somatostatin level was increased in each neuron by NTs.…”
Section: Discussionsupporting
confidence: 81%
“…Whether or not such differences could result from differential distribution of TrkB in both neuronal populations cannot be determined at present, in the absence of evidence involving double labeling for SRIH and TrkB. There are, however, other examples of age-dependent responses to neurotrophins, for instance in the case of neuropeptide Y (NPY) neocortical [28]or hippocampal neurons [27]. An alternate hypothesis is suggested by the fact that the arcuate nucleus contains mostly SRIH interneurons, which do not seem to generate a significant amount of far-reaching projections, and are mainly involved in local communication.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these pathways appear to be involved in GDNF signaling. NPY expression has been shown to be modulated by various growth factors: brain-derived neurotrophic factor in cortical neurons, nerve growth factor in avian sympathoadrenal cells, and GDNF in enteric neurons (Anitha et al, 2006;Barnea et al, 1995;Barreto-Estrada et al, 2003). As NPY was the transcript that was most significantly altered in the budded and nonbudded conditions among nearly 30,000 transcripts, we sought to define the effect of NPY on the budding of the WD.…”
Section: Introductionmentioning
confidence: 99%